The Combination of Problem Based Learning (PBL) And Team Assisted Individualization (TAI) To Learning Activities And Mastering of Hydrocarbon Competencies Class XI MIPA-4 Students of MAN Sampang. - Salim Salim; Siti Rasyida Hidayati (Universitas Lampung, 2021)
This research is a Classroom Action Research that aims to improve learning activities and students' competency mastery of hydrocarbon material through the application of a combination of Problem Based Learning (PBL) and Team Assisted Individualization (TAI). The subjects of this study were 23 students of class XI MIPA-4 MAN Sampang for the 2019/2020 academic year, consisting of 9 boys and 14 girls. This research was conducted in two cycles, each cycle carried out in 3 meetings. The activity stages of each cycle include action planning, action, observation, and reflection. The student activity data collection was carried out through observation. Competency mastery data is carried out using the technical competency tests in the form of subjective tests in the form of descriptions. The research data were processed and analyzed qualitatively. Based on the data analysis, it can be concluded: (1) Student's learning activity in cycle I was 76,43% and cycle II was 87,42% (2) The average value of student competency mastery in pre-cycle was 57,83, cycle I was 73,09 and cycle II of 80,48. (3) Classical completeness of student's learning in the pre-cycle was 34,78%, cycle I was 65,22% and cycle II was 86,96% Keywords: the combination of PBL and TAI, learning activities, mastery of competencies